Arrhythmias in the paediatric intensive care unit: a prospective study of the rates and predictors of arrhythmias in children without underlying cardiac disease. (1st December 2014) - Cassel-Choudhury, Gina N.; Aydin, Scott I.; Toedt-Pingel, Iris; Ushay, H. Michael; Killinger, James S.; Cohen, Hillel W.; Ceresnak, Scott R.
Abstract Objective Arrhythmias are common in patients admitted to the paediatric intensive care unit. We sought to identify the rates of occurrence and types of arrhythmias, and determine whether an arrhythmia was associated with illness severity and paediatric intensive care unit length of stay. Design This is a prospective, observational study of all patients admitted to the paediatric intensive care unit at the Children's Hospital at Montefiore from March to June 2012. Patients with cardiac disease or admitted for the treatment of primary arrhythmias were excluded. Clinical and laboratory data were collected and telemetry was reviewed daily. Tachyarrhythmias were identified as supraventricular tachycardia, ventricular tachycardia, and arrhythmias causing haemodynamic compromise or for which an intervention was performed. Results A total of 278 patients met the inclusion criteria and were analysed. There were 97 incidences of arrhythmia in 53 patients (19%) and six tachyarrhythmias (2%). The most common types of arrhythmias were junctional rhythm (38%), premature atrial contractions (24%), and premature ventricular contractions (22%). Tachyarrhythmias included three supraventricular tachycardia (50%) and three ventricular tachycardia (50%). Of the six tachyarrhythmias, four were related to placement or migration of central venous lines and two occurred during aminophylline infusion. Patients with an arrhythmia had longer duration of mechanical ventilation and paediatric intensive care unit stay (p<0.001). In multivariate analysis, central venous lines (odds ratio 3.1; 95% confidence interval 1.3–7.2, p=0.009) and aminophylline use (odds ratio 5.1; 95% confidence interval 1.7–14.9, p=0.003) were independent predictors for arrhythmias. Conclusions Arrhythmias were common in paediatric intensive care unit patients (19%), although tachyarrhythmias occurred rarely (2%). Central venous lines and use of aminophylline were identified as two clinical factors that may be associated with development of an arrhythmia.